Phononic metastructures with ultrawide low frequency three-dimensional bandgaps as broadband low frequency filter - Muhammad (Sci Rep, 2021)
Vibration and noise control are among the classical engineering problems that still draw extensive research interest today. Multiple active and passive control techniques to resolve these problems have been reported, however, the challenges remain substantial. The recent surge of research activities on acoustic metamaterials for vibration and noise control are testimony to the fact that acoustic metamaterial is no longer limited to pure theoretical concepts. For vibration and noise control over an ultrawide frequency region, 3-D metastructures emerge as a novel solution tool to resolve this problem. In that context, the present study reports a novel proposal for 3-D monolithic phononic metastructures with the capability to induce low frequency ultrawide three-dimensional bandgaps with relative bandwidth enhancements of 157.6% and 160.1%. The proposed monolithic metastructure designs consist of elastic frame assembly that is connected with the rigid cylindrical masses. Such structural configuration mimics monoatomic mass-spring chain where an elastic spring is connected with a rigid mass. We develop an analytical model based on monoatomic mass-spring chain to determine the acoustic mode frequency responsible for opening the bandgap. The wave dispersion study reveals the presence of ultrawide bandgaps for both types of metastructures. The modal analysis shows distribution of vibration energy in the bandgap opening (global resonant mode) and closing (local resonant mode) bounding edges. We further analyze the band structures and discuss the physical concepts that govern such ultrawide bandgap. Vibration attenuation inside the bandgap frequency range is demonstrated by frequency response studies conducted by two different finite element models. Thanks to additive manufacturing technology, 3-D prototypes are prepared and low amplitude vibration test is performed to validate the numerical findings. Experimental results show the presence of an ultrawide vibration attenuation zone that spreads over a broadband frequency spectrum. The bandgaps reported by the proposed metastructures are scale and material independent. The research methodology, modelling and design strategy presented here may pave the way for the development of novel meta-devices to control vibration and noises over a broadband frequency range.